Predictive Capacity of First-Trimester Diagnosis of Placenta Previa - Sarker, Minhazur; Feiner, Rachel; Canfield, Dana; Kent, Madison; Wiley, Rachel; Lamale-Smith, Leah; Teal, Elizabeth N. (American Journal of Perinatology, 2025)
First-trimester transabdominal ultrasound (TAUS) is sometimes used to diagnose placenta previa and counsel patients accordingly. We aimed to determine the predictive capacity of a first-trimester transabdominal ultrasonographic placenta previa diagnosis for persistence to the second trimester.Retrospective cohort study of patients with singleton pregnancies and first-trimester transabdominal ultrasonographic placenta previa diagnoses from January to December 2022. The primary outcome was the predictive capacity of a first-trimester TAUS diagnosis of placenta previa for placenta previa persistence into the second trimester. Secondary outcomes included the predictive capacity of a first-trimester TAUS for placenta previa persistence to delivery and risk factors associated with placenta previa persistence. Chi-square and student's t-test were used to determine statistical significance, and a multivariable logistic regression determined the strength of associations.Of the 185 patients with a first-trimester TAUS diagnosis of placenta previa, 159 (86.0%) resolved by the second-trimester resulting in a predictive capacity for persistence to the second-trimester of 14.0%. Moreover, 182 (98.4%) were resolved by delivery, resulting in a predictive capacity for persistence to delivery of 1.6%. Among the 27 patients with a prior cesarean delivery, the predictive capacity of a first-trimester placenta previa diagnosis for persistence to the second-trimester was 22.2% and to delivery was 7.4%. Advanced maternal age and posterior placenta in the first trimester were risk factors for previa persistence to the second trimester, while prior cesarean delivery and reproductive assistance were not.First-trimester transabdominal ultrasonographic placenta previa diagnosis has a poor predictive capacity for placenta previa persistence to the second trimester and even lower for persistence to delivery. Counseling patients regarding placenta previa diagnosis in the first trimester may result in unnecessary patient anxiety and activity restrictions.
Keywords: first-trimester ultrasound; transabdominal ultrasound; placenta previa; prenatal diagnosis